PENGARUH PEMBERIAN MINUMAN BERENERGI YANG MENGANDUNG ASPARTAM TERHADAP GAMBARAN HISTOPATOLOGI RENAL TIKUS JANTAN (Rattus norvegicus L.) - Cindy Mentari; Des suryani (Universitas Muhammadiyah Sumatera Utara, 2018)
ABSTRACTBackground: Energy drinks containing aspartame are commonly consumed by the public, the use of aspartame in energy drinks causes controversy regarding its safety against kidneys especially when consumed in excess. Objective: This study aimed to determine the effect of energy drinks containing aspartame on histopathology renal male rats (Rattus norvegicus L .)